2019
DOI: 10.1186/s12882-019-1452-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum sclerostin levels are positively related to bone mineral density in peritoneal dialysis patients: a cross-sectional study

Abstract: Background Sclerostin, an antagonist of the Wingless-type mouse mammary tumor virus integration site (Wnt) pathway that regulates bone metabolism, is a potential contributor of chronic kidney disease (CKD)–mineral and bone disorder (MBD), which has various forms of presentation, from osteoporosis to vascular calcification. The positive association of sclerostin with bone mineral density (BMD) has been demonstrated in CKD and hemodialysis (HD) patients but not in peritoneal dialysis (PD) patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Clinical studies have yielded inconclusive findings regarding the relationship between circulating sclerostin levels and iPTH in CKD patients. In dialysis patients, sclerostin was negatively correlated with iPTH [32,33], which may be related to the suppression of sclerostin production by osteocytes, or the decrease of bone mass in secondary hyperparathyroidism [32]. However, we did not observe a correlation between iPTH and sclerostin in CKD patients prior to dialysis, in agreement with previous reports [11,20].…”
Section: Discussionsupporting
confidence: 90%
“…Clinical studies have yielded inconclusive findings regarding the relationship between circulating sclerostin levels and iPTH in CKD patients. In dialysis patients, sclerostin was negatively correlated with iPTH [32,33], which may be related to the suppression of sclerostin production by osteocytes, or the decrease of bone mass in secondary hyperparathyroidism [32]. However, we did not observe a correlation between iPTH and sclerostin in CKD patients prior to dialysis, in agreement with previous reports [11,20].…”
Section: Discussionsupporting
confidence: 90%
“…By binding to LRP5/6 or forming a tertiary complex with LRP5/6, sclerostin and DKK1, respectively, exerted their role in modulating the cross-talk of CKD-related bone disease and vasculatures with the results of vascular smooth muscle cells trans-differentiation and vascular calcification [7,11,15,31]. Thambiah et al and Kuo et al conducted studies in patients of advanced renal disease and PD and found a positive correlation between serum levels of sclerostin and bone mineral density (BMD) [31,32]. By intervention with an anti-resorptive agent, Miyaoka et al found denosumab had reno-protective effects with the reverse of the age-related decrease of eGFR by inhibiting bone resorption and suppressing seral phosphate load in non-CKD patients [33], which indicated a possible role of manipulating sclerostin toward renal or vascular protection.…”
Section: Discussionmentioning
confidence: 99%
“…There is some controversy as to whether circulating Wnt inhibitors exert a direct effect on bone metabolism, partly due to the discrepancy between plasma levels of sclerostin and bone BMD. Even though sclerostin is a negative regulator of bone formation, a positive correlation between plasma levels of sclerostin and bone BMD has been reported in general population and CKD cohorts (CKD3 to CKD5 dialysis) [113][114][115][116][117][118][119][120]. These results question the role of circulating sclerostin in bone turnover and suggest that sclerostin may primarily exert paracrine signaling.…”
Section: Calcified Vasculature Affects Bone Metabolismmentioning
confidence: 97%